2017
DOI: 10.3389/fpls.2017.01580
|View full text |Cite
|
Sign up to set email alerts
|

Root Damage under Alkaline Stress Is Associated with Reactive Oxygen Species Accumulation in Rice (Oryza sativa L.)

Abstract: Alkaline stress (high pH) severely damages root cells, and consequently, inhibits rice (Oryza sativa L.) seedling growth. In this study, we demonstrate the accumulation of reactive oxygen species (ROS) in root cells under alkaline stress. Seedlings of two rice cultivars with different alkaline tolerances, ‘Dongdao-4’ (moderately alkaline-tolerant) and ‘Jiudao-51’ (alkaline-sensitive), were subjected to alkaline stress simulated by 15 mM sodium carbonate (Na2CO3). Alkaline stress greatly reduced seedling surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(110 citation statements)
references
References 59 publications
3
107
0
Order By: Relevance
“…This result could be explained through the osmotic stress effects of plant root growth [24]. Previous work showed that salt stress conditions had a suppression role in the growth of plants [25]. Similar results were obtained in our present study.…”
Section: Discussionsupporting
confidence: 92%
“…This result could be explained through the osmotic stress effects of plant root growth [24]. Previous work showed that salt stress conditions had a suppression role in the growth of plants [25]. Similar results were obtained in our present study.…”
Section: Discussionsupporting
confidence: 92%
“…Our results were in agreement with the findings of Kumar et al [32] in chickpea, Sita et al [30] in lentil, and Hu et al [21] in tall fescue, who reported higher EL under heat stress. The increase in lipid peroxidation might be as a result of the overproduction and accumulation of ROS, which then causes membrane peroxidation, protein degradation, and DNA damage to severely inhibit growth [33][34][35]. Consequently, our results revealed that heat stress highly damaged the membrane integrity and stability of alfalfa, especially heat-sensitive cultivars.…”
Section: Discussionmentioning
confidence: 73%
“…This suggests that the above parameters of root growth (i.e., Na + content in underground tissue and the length of new roots) can be regarded as the primary indicators for evaluating salt tolerance capacity of wetland plant species. Due to the direct contact with salt, the first organ to be affected by saline and alkaline stress is underground tissue (i.e., root) [61]. The existing salt on the outside of roots has an immediate effect on cell growth and associated metabolism [55].…”
Section: Principal Component Analysis (Pca) For Selecting Salt Toleramentioning
confidence: 99%